Disillusion Of Marital Life In Gustave Flaubert's Madame Bovary Novel (1856): A Psychoanalytic Approach - Chotimah, Vika Chosnul (2012)
This research paper elaborates the portraits of disillusion of marital life in Gustave Flaubert's Madame Bovary novel, that are analyzed through psychoanalytic approach. The objectives of the research are to analyze the structural elements of the novel and to analyze the novel based on psychoanalytic approach by identifying the relationship between the novel and the personality of the major character of the novel. This research belongs to a qualitative research. The data of the research is the text of a novel entitled Madame Bovary. Whereas the data source comes from both primary data source which is in the form of the text of the novel being researched and secondary data source such as biography of the author, websites and other sources about the novel, the approach and the personality of the major character that support the analysis. The method to analyze the data is descriptive analysis. Having analyzed the novel, the researcher comes to the conclusions as follows: the disillusion of Emma Bovary is caused by her unfulfilled need. The basic needs of Emma Bovary is actually a careness of her husband. It shows when Emma Bovary needs something but her husband does not comprehend her. She uses many reactions to reduce her disillusion. Those are repression, denial, fantasy, and reaction formation.